Heart Failure with Mid-Range Ejection Fraction - State of the Art - Mesquita,Evandro Tinoco (2019)
Abstract In 2016, the European Society of Cardiology (ESC) recognized heart failure (HF) with ejection fraction between 40 and 49% as a new HF phenotype, HF with mid-range ejection fraction (HFmrEF), with the main purpose of encouraging studies on this new category. In 2018, the Brazilian Society of Cardiology adhered to this classification and introduced HFmrEF in Brazil. This paper presents a narrative review of what the literature has described about HFmrEF. The prevalence of patients with HFmrEF ranged from 13 to 24% of patients with HF. Analyzing the clinical characteristics, HFmrEF shows intermediate characteristics or is either similar to HF with preserved ejection fraction (HFpEF) or to HF with reduced fraction (HFrEF). Regarding the prognosis, HFmrEF’s all-cause mortality is similar to HFpEF’s and lower than HFrEF’s. Studies that analyzed cardiac mortality concluded that there was no significant difference between HFmrEF and HFrEF, both of which were lower than HFpEF. Despite the significant increase of publications on HFmrEF, there is a great scarcity of prospective studies and clinical trials that allow delineating specific therapies for this new phenotype. To better treat HFmrEF patients, it is fundamental that cardiologists and internists understand the differences and similarities of this new phenotype.